2013
DOI: 10.5505/tjoncol.2013.914
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Re-Mission video game on the quality of life of adolescents with cancer

Abstract: OBJECTIVESTo determine the effects of Re-Mission video-game on the quality of life of adolescents cancer patients. METHODSStudy was conducted on 61 adolescents their ages ranging between 13 to 18 years, treated between December 2009 and May 2011 years, at two hospitals in Istanbul. Adolescents were divided into control (n=30) and cases group (n=31). Data were collected by the patient information form, FACT-G Quality of Life Scale and Re-Mission Assessment Scale. Data were evaluated in regard with appropriate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Since adolescents experience many physical, social, and psychological changes, focusing on provision of care, preventing health problems, and improving health of adolescents will enable us to assess their quality of life accurately (Yılmaz and Hacıalioğlu, 2018). One of the groups that can best identify the children with problems in school age is nurses (Kurt and Savaşer, 2013). A school health nurse makes physical and mental assessments of the student, plans training for both students and school staff, provides effective communication with parents, identifies school health problems, and implements early diagnosis and treatment (Öncel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since adolescents experience many physical, social, and psychological changes, focusing on provision of care, preventing health problems, and improving health of adolescents will enable us to assess their quality of life accurately (Yılmaz and Hacıalioğlu, 2018). One of the groups that can best identify the children with problems in school age is nurses (Kurt and Savaşer, 2013). A school health nurse makes physical and mental assessments of the student, plans training for both students and school staff, provides effective communication with parents, identifies school health problems, and implements early diagnosis and treatment (Öncel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that interventions implemented for the children with cancer are effective in increasing their quality of life (Beulertz et al, 2016; Shoshani et al, 2016; Stokke et al, 2015). Although there are Turkish studies that show that the interventions implemented for children with cancer do increase their quality of life, no systematic review or meta‐analysis exists that presents all such studies in their entirety (Çetinkaya & Kurt, 2010; Kerimoğlu Yıldız, 2018; Kudubes et al, 2019; Kurt & Savaşer, 2013; Yildiz Kabak et al, 2019) The present systematic review and meta‐analysis aimed to analyse the effects of administered interventions on the quality of life of children with cancer in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…That is why looking for creative ways to offer treatment information that is understandable to children/adolescents and does not make them afraid is of particular relevance to healthcare specialists. Digital games have proved to be an interesting media to transmit the desired information to children in a way that is well received by them (Kurt & Savaser, 2011).…”
Section: Digital Games As Media For Persuasionmentioning
confidence: 99%
“…The narrative of the game (the role of the main character, which is his/her mission, and the human body as the game space) is therefore also relevant, as it involves the players in a vicarious experi- ence that motivates. Research on Re-Mission has indeed shown that it is effective in increasing adherence to treatment among its players (Kurt & Savaser, 2011).…”
Section: Digital Games As Media For Persuasionmentioning
confidence: 99%